Strategi Perencanaan Komunikasi Dakwah Masjid Peneleh Surabaya - A. Fikri Amiruddin Ihsani; Novi Febriyanti (Institut Agama Islam Tribakti (IAIT) Kediri, 2021)
This study discusses the da’wah communication planning strategy of the Peneleh Mosque in Surabaya. The purpose of this research is to describe, explain, and know the strategy of communication planning for the da'wah communication of the Peneleh Mosque in Surabaya and to describe, explain, and know the strategy for the communication planning of the Peneleh Mosque in Surabaya in a review of Talcott Parsons' functional structural theory. This research uses qualitative research methods with a descriptive approach. Data collection techniques used were observation, interviews, and documentation. The data that has been collected are then analyzed, compared, and combined to form a systematic, coherent and complete study result. In this research, it is found that; (1) In the communication planning strategy of the Peneleh Mosque in Surabaya, it takes the subject of preaching from outside, the message design continues the walisongo method, the media used is face-to-face, and the determination of the audience is the surrounding community. (2) In a review of Talcott Parsons' functional structural theory, the strategy for the communication planning of the Peneleh Mosque in Surabaya includes adaptation to the surrounding environmental conditions, achieving the goal of the message content of ritual and social piety, integration between the community, the mosque as a place of worship, and the tahfidz Islamic boarding school. Next, in maintaining the pattern, always carry out active and intensive communication with all existing structures and functions in the Peneleh Mosque area of Surabaya. Thus, it is hoped that the process of da'wah communication can be established effectively and efficiently.